3D‐1D Heterostructure of CoZn Oxyphosphide Nanosheets Anchored on Carbon Nanotubes as Electrocatalysts for the Oxygen Evolution Reaction. Issue 18 (20th July 2018) - Xu, Hui; Zhang, Ke; Liu, Chaofan; Tian, Lin; Du, Yukou
Abstract: Realizing high‐efficiency electrochemical transformation of water is of paramount significance in the field of energy storage and conversion but still a major challenge. Herein, we successfully design and fabricate a class of 3D‐1D heterostructure of 3D CoZn oxyphosphide nanosheet assemblies anchored on 1D carbon nanotubes through a facile one‐pot method. Interestingly, owing to the doping of phosphorus atoms, modified electronic structures, as well as high surface areas, the well‐designed 3D‐1D CoZnP/CNTs nanohybrids exhibit excellent electrocatalytic performances toward oxygen evolution reaction, which needs an overpotential of only 281 mV to achieve a current density of 10 mA cm −2 and exhibits no evidences for activity degradation for 24 h, holding great potentials for acting as highly efficient electrocatalysts for the oxygen evolution reaction. This work may offer new options for constructing promising nanocatalysts with well‐defined heterostructure for water splitting and beyond. Abstract : Multidimensional assemblies : a 3D‐1D heterostructure of 3D CoZn oxyphosphide nanosheets anchored on carbon nanotubes is designed as catalyst for oxygen evolution reaction. Owing to the doping of phosphorus atoms, modified electronic structures, as well as high surface area, the designed 3D‐1D CoZnP/CNTs nanohybrids exhibit excellent electrocatalytic performances toward oxygen evolution reaction.